KNJIŽEVNI POUK V OSNOVNI ŠOLI – ANALIZA UČNEGA NAČRTA SLOVENŠČINA (2011) (Philological Studies, 2019)
Education in Slovenia started as Pre-school Education with the first (from 1st–3rd years) and second age group (from 3rd–6th). Primary School is compulsory and starts from 6th till 15th and has 9 classes is divided into cycles 1st from 1–3 grade, 2nd from 4–6 grade and 3rd from 7–9 grade. After primary school is secondary education that is not (yet) compulsory and after that university. Most of the children attended preschool that combines education and care. Curriculum for Preschool (1999) base on objectives, contents and activities for first (1st till 3rd) and second (3rd till 6th) age group. Curriculum is national document and have sixth subjects: art, language, mathematics, nature, physical education and society. Literature in Preschool is part of Language arts subject. Curriculum for Primary School is Slovenian or Language Arts (2011) is divided in Language and Literature. Subject is mother tongue for most pupils and obligatory subject. Theoretical approach on that based Teaching Literature in Preschool and Primary School is reception theory on Wolfgang Iser (The Act of Reading: a theory of aesthetic response, 1978) and Hans Jaus Robert (Aesthetic experience and literary hermeneutics, 1982) in curriculum 1998 and 2011. In latest decade a leading literary didactic Boža Krakar Vogel (Poglavja iz književne didaktike, 2004 [Chapters from Teaching Literature]) is considering amending the paradigm from reception theory via literary system (Marijan Dović Slovenski pisatelj, 2007 [Slovenian writer]; Itamar Even Zohar Polysystem studies, 1990, 1997) to systemic literary didactic.
Keywords: preschool, primary school, children’s literature, teaching literature, receptionist literary didactic, systemic literary didactic